Alphabetical Compilation and Reformist Thought: A Socio-Historical Study of Abdul Latif Syakur’s Lathaif al-Ahadith al-Nabawiyah in Early Twentieth-Century Minangkabau - Febriyeni; Febrianta, Rita (Institut Agama Islam Negeri (IAIN) Curup, 2026)
This study critically analyzes Lathaif al-Ahadits al-Nabawiyah (1926), a unique hadith compilation authored by Abdul Latif Syakur, a reformist scholar from early 20th-century Minangkabau. The research problem focuses on how this work reflects local Islamic intellectualism and reformist thought through its unconventional structure and socio-religious content. Using a qualitative socio-historical approach that combines textual criticism and interpretive analysis, the study draws on two extant volumes of the book and relevant secondary literature. The findings reveal that Syakur employed an innovative alphabetical arrangement of hadiths based on the Arabic verb prefix in the matn, and incorporated Malay-Jawi commentary to make the text accessible to the local Muslim audience. Thematically, the book addresses issues of ritual, ethics, gender, and social reform, reflecting the author's moderate stance in navigating the tensions between traditionalism and modernism. The study concludes that Lathaif al-Ahadits al-Nabawiyah represents an important contribution to localized Islamic knowledge production in Southeast Asia and exemplifies how vernacular scholarship engaged with both classical traditions and modern social contexts.